The Benefit of the Doubt: Patent Examination Under Strategic Obfuscation - Figueroa, Nicolás; Lemus, Jorge (Management Science, 2023)
An applicant privately observes the value of an idea and files a patent application. After the examination, the patent examiner may not find conclusive evidence of the idea’s value. In this case, granting a patent can be the right decision or a mistake. Moreover, it can prompt obfuscation—effort to disrupt communication—by the applicant, reducing allocative efficiency. We show there is more obfuscation when examiners are more lenient, and we provide an empirical exercise supporting this conclusion. We also show that more examination resources do not prevent and may lead to more obfuscation. This result continues to hold when applicants can invest in knowledge to increase their chances of having good ideas. We also show that there is less obfuscation when good ideas are harder to find. This paper was accepted by Ilia Tsetlin, behavioral economics and decision analysis. Funding: N. Figueroa gratefully acknowledges financial support from ANID PIA/APOYO AFB220003. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.00140 .